The effects of RRI-oriented roadmapping on the digital transformation of regions - Sabine Neuberger; Manfred Paier; Marianne Hörlesberger (Journal of Responsible Innovation)
Responsible Research and Innovation (RRI) is a policy concept with the potential to support regional development and thus can guide the digital transformation of traditional industry regions. The DigiTeRRI project developed RRI-oriented roadmapping and applied it in three traditional industry regions in Austria, France, and Sweden. This research aimed to assess the effects of RRI-oriented roadmapping on advancing digital transformation in such traditional industry regions. Survey results showed that the digital maturity of organizations improved in the three pillars, i.e. Culture & skills, Infrastructure & technologies, and Ecosystem. Furthermore, the results indicate that RRI-oriented roadmapping had a positive effect in advancing the digital transformation of the three regions. This research adds to the literature on the RRI concept through the practical application of roadmapping to support the digital transformation of regions.